The selected properties of hybrid particleboard made from oil palm empty fruit bunch (EFB) and merpauh (Irvingla Malayanan Olive) sawdust wastes - Hamid, Norul Hisham; Yazid, Mohd Fitri; Hassan, Noraishah; Mokhtar, Mohd Afiq (Knowledgia Scientific, 2015)
The physical and mechanical properties of particleboard made from Merpauh (Irvingla malayana olive) and empty fruit bunch (EFB) wastes mixture was investigated in relation to the fibre diameter and mixture ratio. The EFB and Merpauh particles with diameter of less than 1 mm and more than 1 mm were prepared and they were mixed with ratios of 40:60, 60:40, 80:20, 100:0 separately. The particleboard sized of 340mm x 340mm x 12mm was prepared with a target density of 750 Kg/m3 contained 12% urea formaldehyde (UF) resin, 3% hardener and 1% wax. The water absorption, thickness swelling, modulus of rupture, modulus of elasticity and internal bond were tested in according to JIS (Japanese Industrial Standard): 5908. The results showed that the thickness swelling and modulus of elasticity of any mixture (EFB/wood) or homogenous EFB particleboards were not met a minimum requirement of JIS 5908: 2003 standard. In contrast, only modulus of rupture and internal bonding (thin particle) met a minimum standard.